Structural identification of N-glycan isomers using logically derived sequence tandem mass spectrometry - Chia Yen Liew (Nature Portfolio, 2021)
Mass spectrometry can be used for structural determination of N-glycans, but commonly requires prior derivatisation or comparison to a library of standards. Here logically-derived sequence tandem mass spectrometry allows for assignment of native N-glycans by analysis of successive fragmentation patterns without derivatisation and standards.